IMPROVING INDONESIAN LANGUAGE LEARNING OUTCOMES USING THE PRINCIPAL MATERIAL OF READING SHORT STORY TEXTS THROUGH THE APPLICATION OF THE RECITATION METHOD - Devinna Riskiana Aritonang, Hanifah Parapat, (PANTAK: Jurnal Penelitian Tindakan Kelas, 2024)
The aim of this research is to improve the Indonesian language learning outcomes of students in class XI Semester One of Padangsidimpuan Muhammadiyah High School with the material of reading short story texts. The type of research used is classroom action, and the research method used is descriptive. 34 students in class XI of Padangsidimpuan Muhammadiyah High School were the research subjects. The direct observation method is used. Observation sheets made by teachers and students function as data collection tools. This research was conducted in two cycles, with planning, implementation, observation and reflection stages. The results of Classroom Action Research on Indonesian language subjects regarding reading short story texts using the Recitation method are as follows: in cycle I, learning outcomes showed an average score of 78.20, and in cycle II, learning outcomes showed an average score of 83, 41. Based on the research results, it can be concluded that applying the recitation method in learning Indonesian can improve Indonesian language learning outcomes with the main material being reading short story texts for class XI students at SMA Muhammadiyah Padangsidimpuan which is successful.